The Urgency of Legal Protection for Victims of Cyberbullying in Indonesia - Sitihastuti, Sholikah; Solikhah, Solikhah (Jurnal Cakrawala Hukum, 2024)
The study aims to analyze the urgency of legal protection for victims of cyberbullying in Indonesia. The method used is normative law based on legal materials (library based), including primary and secondary legal materials that produce information in the form of notes and descriptive data contained in the text under study. The author uses a qualitative approach based on the initial step taken by collecting the necessary data, then classifying and describing. Based on the research conducted, it can be concluded that the regulations in place are still not providing adequate legal protection for victims of cyberbullying. Although the crime of cyberbullying is regulated in the Criminal Code and the Information and Electronic Transactions Law, the regulation is more focused on taking action against the perpetrators. Therefore, it is necessary to expand and improve the legislation to provide a stronger guarantee of legal protection for victims of cyberbullying. This legal protection must include prevention, detection, handling, and recovery efforts for the victims. How to cite item: Sitihastuti, S., & Solikhah, S., Mohammad Haris Yusuf Albar, and Agung Mafazi. â€œThe Urgency of Legal Protection for Victims of Cyberbullying in Indonesia.â€ Jurnal Cakrawala Hukum 15 no. 1 (2024): 61-68. DOI: 10.26905/idjch.v15i1.12025.